Assessment of pesticides use effects on honeybee colonies and its financial impact in some selected districts of Bale Zone, South Eastern Ethiopia - Bekele Tesfaye; Genet Dadi; Wondimu Lelisa; Temaro Gelgelu (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2021)
The existence of honeybees in the ecosystem has a significant effect in worldwide agricultural production. While searching for food, the honeybee is often exposed to several contaminants or poisoning materials such as plant protection products like pesticides. The aim of this work was to assess and identify the effect of commonly used pesticides from various groups (herbicides, insecticides, and fungicides) on honeybees' health and their products. For the study, purposive sampling was used in selecting the districts and Rural Kebeles (RKs) while random sampling was used in selecting sample enumeration sites and respondents from each household. For the analysis, SPSS statistical software package version 20 and descriptive statistics were used to determine the effects of pesticides on honeybees. The result showed that from a total of 138 farmers interviewed, 97.1% were pesticide users. Out of the total pesticides used in the area, it was categorized 55.80% as herbicides, 18.80% as insecticides, and 25.36% as fungicides. The current assessment indicated that 72.46% of pesticides were applied in the main cropping season and only 27.54% applied in the second cropping season and 50% of them have chosen early morning (6:00-12:00 am) as an appropriate time to spray. According to this study, 66.67% apply pesticides before the crops blooming, 30.43% both before and during the crops on blooming, and 2.90% of farmers were non-chemical users. As sample respondents reported only 50.7% of the beekeepers located their apiary site by considering the distance between the apiary site and farmland. The current assessment showed that as a negative result of pesticides on honeybees 914, 1012, and 335 loss were recorded due to mass dead, absconded, and dwindled in the study area respectively. It was also assessed that the economic loss that occurred was anticipated due to the honeybees colony dead, absconded, and dwindled were 198,728.15, 220,922.45, and 73,227.49 US$ respectively in the study districts. The result revealed that 71.7% of sample respondents are not aware of the proper use of pesticides. Therefore, it is important to note that well programmed and organized training is required for both crop producers and beekeeper farmers in Ethiopia and particularly in Bale where the belt of wheat and barley production is very high and requires heavy pesticides.